A study of voltage dips, and method to improve the performance of adjustable speed drives (ASD'S) during voltage dip / N Perumal and Mohammad Afzan Amir Hamzah - N, Perumal; Amir Hamzah, Mohammad Afzan (2004)
This paper discusses issues of power quality in general, and voltage dips in particular. Voltage dips is one of the major power quality problems for users of electrical energy causing sensitive equipments like Adjustable Speed Drive (ASD) and process control equipments to malfunction Investigation into the causes of voltage dips and their impact on the performance of ASD during voltage dips, looking into different possibilities to reduce the problems caused by voltage dips and methods to improve the performance of ASD during voltage dips are discussed in this paper. The main focus of the study is the redesign of ASD by introducing boost converter in the system without any additional energy storage devices. A case study has been performed at the Filrexbercham Industry in Ipoh, where voltage dips causes problems, Different values of voltage dips and boost converters were simulated using the simulation program MATLAB/Power System Blockset. The simulation results presented shows that boost converters provide ride-through to critical ASD loads during voltage dips as well as an improvement in the power quality.